The Implementation of the Iddah Period for Men: A Mediation Mechanism to Prevent Divorce - Anugerahayu, Ayang Afira; Fangggi, Prandy Arthayoga Louk (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
This study aim to analyze the implementation of a waiting period (iddah) for men as mechanism for preventing divorce in Indonesia, in line with Circular Letter of the Director general of Islamic Community Guidance No. P-005/DJ.III/Hk.00.7/10/2021. The research employs a normative legal method by examining regulations related to the waiting period as stipulated in the Compilation of Islamic Law (KHI), the Marriage Law, and classical fiqh. It applies a comprehensive approach combining Islamic legal sources, the statute approach, the conceptual approach, and the social approach. The findings indicate that, functionally, the proposed idea aligns with the concept of Syibh al-Iddah (waiting period), which is derived from the principles of maslahah mursalah (public benefit) and maqāṣid al-sharī‘ah (objectives of Islamic law). This concept also resonates with the practice of mandatory mediation already regulated under Indonesian positive law. The study concludes that although the idea lacks a normative basis in classical fiqh, its application represents a progressive and effective step. The waiting period provides space for both parties to reflect, manage emotions, and potentially achieve reconciliation. This is reinforced by recent regulations issued by the Supreme Court and the Directorate General of Islamic Community Guidance, which de facto have already implemented such a waiting period for men. Therefore, the formal application of this mechanism, even without employing the terminology of iddah, serves as a strong instrument to preserve family integrity and reduce divorce rates.